Preparation of BiVO4/MIL‐125(Ti) composite with enhanced visible‐light photocatalytic activity for dye degradation. (8th February 2018) - Yang, Zhiquan; Ding, Jie; Feng, Jinna; He, Chong; Li, Ying; Tong, Xiaowen; Niu, Xiaojun; Zhang, Hongguo
Abstract : Because of their desired features, including very specific surface areas and designable framework architecture together with their possibility to be functionalized, Metal Framework (MOF) is a promising platform for supporting varied materials in respect of catalytic applications in water treatment. In this work, a novel visible‐light‐responsive photocatalyst that comprised BiVO4 together with MIL‐125(Ti), was synthesized by a two‐step hydrothermal approach. The characterization of as‐obtained samples as performed by X‐ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, Fourier transform infrared spectroscope, X‐ray photoelectron spectroscopy and ultraviolet‐visible diffuse reflection spectra. Rhodamine B was selected being a target for the evaluation of the photocatalytic function of as‐developed photocatalyst. The photocatalytic reaction parameters, for example, the content of BiVO4 as well as initial concentration of Rhodamine B was researched. The composite photocatalyst possessing Bi:Ti molar ratio of 3:2 brought to light the fact that the greatest photocatalytic activity had the ability to degrade 92% of Rhodamine B in 180 min. In addition to that, the BiVO4 /MIL‐125(Ti) composite could keep its photocatalytic activity during the recycling test. The phenomenon of disintegration of the photo‐generated charges in the BiVO4 /MIL‐125(Ti) composite was brought to discussion as well. Abstract : A novel visible‐light responsive photocatalyst of BiVO4 /MIL‐125(Ti) was synthesized via a two‐step hydrothermal method. The BiVO4 /MIL‐125(Ti) composite shows prior photocatalytic performance than parent materials. The enhancement of catalytic activity was attributed to the increasing separation rate of photogenerated charge carriers based on the formation of interface between BiVO4 and MIL‐125(Ti).